Infusion of islamic values and ethics in scools curriculum: The role of teachers - Rahimah, Embong; Elsayed, Ragab; Nashat, Biomy (2016)
Values act as a standard for anything that, humans do desire and wish for, whether it can be seen, heard or felt by our senses. It shows the direction and determines the way choices are made and actions are carried out. It also tells the person what to do and what not to do in a given society. The aim of values education is to encourage young people's awareness of having values and their corresponding relationship to the world in which they live. Therefore, this paper present and discusses the values and ethics in Islam its forms and sources. The paper further shade more lights on the infusion of Islamic values and ethics in schools curriculum, the role of teachers, challenges faced in infusing Islamic values in schools curriculum. The paper concludes with some recommendations for addressing the challenges with a view to achieve the desired goals of the present day education systems.